Learning by Design: Educational Environments as Tools for Pre-School Education - Ozaeta, Emilio U. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2013)
This theoretical paper poses the possibility of learning environments becoming spatial learning aids, particularly in the spatial cognitive development process. Through a survey of research in the area of spatial intelligence and cognition in educational psychology the author establishes the foundation for this possibility. The paper concludes with a proposed initial set of designed principles for pre-school environments based on the research in that field.